Income distribution changes and their impact in the post- World War II period - Giovanni Andrea Cornia; Tony Addison; Sampsa Kiiski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper analyses the trends in within-country inequality during the post- World War II period, with particular attention to the last 20 years, on the basis of a review of the relevant literature and of an econometric analysis of inequality trends in 73 countries accounting for 80 per cent of the world's population and 91 per cent of world GDP-PPP. The paper suggests that the last two decades have been characterized by a surge in within-country inequality in about two-thirds of the developing, developed and transitional nations analysed. It also suggests that in those countries where the upsurge in inequality was sizeable or where inequality rose from already high levels, growth and poverty alleviation slowed down perceptibly. While this trend towards higher inequality differs substantially across countries in its extent, timing and specific causes, it marks a clear departure from that observed during the first 30 years of the post-World War II period during which, with the exception of Latin America and parts of Sub-Saharan Africa, a widespread move towards greater egalitarianism was noted in the majority of the socialist, developing and industrialized economies. – inequality ; poverty reduction ; policy reform ; egalitarian growth
Keywords: D30; N30; O57; 330; Einkommensverteilung; Welt